PENGARUH LEVERAGE, PROFITABILITY, UKURAN PERUSAHAAN DAN PROPORSI KEPEMILIKAN INSTITUSIONAL TERHADAP TAX PLANNING - Saragih, Afni Eliana; Sembiring, Yan Christin Br; Purba, Maria Rani Fransiska Br (Jurnal Riset Akuntansi & Keuangan, 2023)
This study aims to examine the effect of leverage, profitability, company size and the proportion of institusional ownership on tax planning in basic indusrtrial and chemical companies listed on Indonesia Stock Exchange (IDX) in the period of year 2018-2021. The sampling technique was purposive sampling in accordance with predetermined criteria, in order to obtain 27 sample companies with a research period of 4 years, so that the total sample data was 108 data. Based on the results of multiple linear regression analysis, it can be concluded that leverage has a positive and insignificant effect on tax planning. Profitability has a negative and insignificant effect on tax planning. Company size has a positive and significant effect on tax planning. The proportion of institutional ownership has a positive and insignificant effect on tax planning